The Implementation of Contractor Safety Management System to Prevent Work Accidents at Coal Mining Company - Nadia Nur Amalina; Hanum Elok Larasati (Universitas Airlangga, 2020)
Introduction: The coal mining company is a company that plays an important role in the Indonesia’ economy, but it is one of the high potential risk industry because most of its activities are carried out by contractors who generally undisciplined and have a lack understanding of Occupational Safety and Health. To solve this problem, the Contractor Safety Management System (CSMS) program must be conducted. The purpose of this study was to determine the implementation of CSMS program in a coal mining company in Indonesia. Methods: This cross-sectional study was conducted at a coal mining company in South Kalimantan in 2017 and analyzed descriptively. The CSMS stages and its program were obtained by direct observation using checklist sheets and study documents. Results: The CSMS procedure at the coal mining company started with risk assessment, pre-qualification, qualification, pre-work, monitoring and evaluation activities. To increase the effectiveness of the OSH program, the coal mining company also conducted additional activities such as supervisor competency training, general morning talk, technology guidance, audits and occupational safety health as well as environment seminars. Work accidents rate at three main contractors in the coal mining company was effectively reduced after an audit and improvement of the implementation of CSMS in 2016. Conclusion: CSMS activities in coal mining company have been carried out routinely and systematically where monitoring activities are carried out by coal mining company’s and sub/contractors’s QHSE officer, and the implementation of CSMS that is consistent and fit to the standards in 2016 proven to reduce the work accident rates in the coal mining company. Keywords: coal mining, contractor safety management system, work accident prevention